HUBUNGAN TINGKAT PENGETAHUAN SISWA DAN PERAN ORANGTUA DENGAN PERILAKU MEMBUANG SAMPAH SEMBARANGAN PADA SISWA SEKOLAH DASAR DI TANGERANG - Dea Amalia; Yuni Susilowati; Lastri Mey Winarni (Nusantara Hasana Berdikari, 2021)
School-age children who have a habit of throwing garbage in vain will cause a variety of health problems and environment especially in school environments that can interfere with the teaching and learning process becomes uncomfortable. Objective: Know the student's level of knowledge and parental role in the behavior of throwing garbage in elementary school students. Methods: Quantitative research with Crossectional approaches. Sampling techniques using incidental sampling. Samples of research 110 students,I grade V and VI elementary schools who have filled in questionnaires through Google form. Result: Respondents ' knowledge rate was less than 56 respondents (50.9%). A large role of parents of good respondents is as much as 61 respondents (55.5%). Most are well-behaved in dumping garbage, which is 62 respondents (56.4%). Conclusion: The Chi-square test obtained P-value 0.020 < 0.05 Ho rejected then there is a significant relationship between the level of knowledge of students with the behavior of throwing garbage. Chi-square test obtained P-value 0.048 < 0.05 Ho rejected then it can be concluded there is a significant relationship between students ' parental role level with the behavior of throwing waste. Conclusion: Students who have good knowledge and students who have a good parental role have good behavior in removing garbage. Advice: It is expected for students to pay attention to and maintain the cleanliness of the environment, for parents and teachers are expected to further improve the supervision of students in order to maintain the cleanliness of the environment not to dispose of garbage.